Studies on the Processing and Shelf Life of Low - Fat Chevon Patties with Preservatives - J., Indumathi; P.R.S, Moorthy; K., Sudhakara Reddy; A. , Jagadeesh Babu (Journal of Meat Science, 2011)
Refrigerated storage (4 ± 1°C) of lowfat chevon patties prepared from the pre-blended ground chevon with 0.25 percent sodium alginate (SA) alone or in combination with 0.1% ascorbic acid (AA) or 0.25 percent citric acid (CA) indicated that SA+CA samples had a significant lower pH, microbial load and higher tenderness scores compared to the other samples. On the other hand, the SA + AA samples had a lower TBARS values compared to the other samples. Irrespective of the formulations, there was a significant increase in hardness, pH, TBARS values and SPC values with increase in storage period, but psychrophiles and yeasts and moulds could not be detected in any of the product through out the storage period. On the other hand, for all the formulations, no significant change was observed in moisture, protein and fat contents through out the storage period. Organoleptic evaluation revealed that, the storage had significantly (p<0.05) reduced the mean color, flavor juiciness, tenderness and overall acceptability scores of all the formulations of low-fat chevon patties from 0 to 20th day.